Nuclear ferromagnetism - Frohlich, H; Nabarro, F.R.N. (Physical Society, 1947)
It is shown that at sufficiently low temperatures metals become ferromagnetic owing to an orientation of the nuclear spins. The domain structure of such ferromagnetics is analogous to that of ordinary ferromagnetics.
Keywords: nuclear ferromagnetism